ChemInform Abstract: A Ruthenium‐Catalyzed Coupling of Alkynes with 1, 3‐Diketones. Issue 9 (5th March 2013) - Pennington‐Boggio, Megan K.; Conley, Brian L.; Williams, Travis J.
Abstract Ene‐type coupling reactions of alkynes with 1, 3‐diketones proceed at mild temperatures under air and in the presence of water.